Redescription of the subgenus Rhithrogeniella Ulmer 1939 (Ephemeroptera, Heptageniidae, genus Ecdyonurus) based on reared specimens from India and Thailand - Kluge, Nikita; Sivaruban, T.; Srinivasan, Pandiarajan; Barathy, S.; Isack, Rajasekaran (Zootaxa, 2023)
Rhithrogeniella Ulmer 1939 is treated here as a subgenus of the genus Ecdyonurus Eaton 1868 (s. l.). The subgeneric name Rhithrogeniella is a senior synonym of Afghanurus Demoulin 1964 syn. n., Paracinygmula Bajkova 1975 syn. n. and Nixe Flowers 1980 syn. n. Additional description of Ecdyonurus (Rhithrogeniella) ornatus (Ulmer 1939) is given based on imagines and subimagines of both sexes reared from larvae in India and Thailand; lectotype of this species name is designated. Synonymy of E. (Rh.) ornatus and E. (Rh.) tonkinensis Soldán & Braasch 1986 is established (syn. n.). Male and female imagines and subimagines of an unnamed species of Rhithrogeniella are reported from India.